ON (sub- super) asymptotic martingales - Hassan H- Ebrahem; Juwan Abbas-Ali (Tikrit Journal of Pure Science)
In this paper we intoduce a new class of definitions (sub - super) asymptotic martingale through the concept of asymptotic martingale. we investigate and prove some properties of asymptotic martingale and (sub - super) asymptotic martingale .